PETROLOGY AND GEOCHEMISTRY OF GRANITIC PEBBLES IN THE PARNASSOS FLYSCH AT ITI MOUNTAIN, CONTINENTAL CENTRAL GREECE - Karipi, S.; Tsikouras, B.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2007)
Granite rocks occur as pebbles within the Parnassos flysch deposits, in the area of Iti (Central Greece). The granites are per aluminous, calcic rocL· with S-type characteristics. Geochemical features reveal that these rocL· are not co-genetic to the Iti ophiolite but they have been derived from magmas affected by a subduction component. They display common characteristics with VAG-type lithologies. Geochemically, they mostly resemble nearby granite clastsfrom a Triassic flyschoid from Evia (Liri Unit), and lesser those within the Parnassos flysch at Amfissa and Pliocene fluvial deposits at Patras